De (pre)potência Olímpica à invenção do país do futebol: a política para os esportes do governo Emílio Garrastazu Médici (1969-1974) - Ferreira, João Fernando Pelho (2014)
This thesis is concerned with the policy faced to Physical Education and to sports, with the most attention to the soccer, in the government of Emilio Garrastazu Médici, contrasting the military training of the technical committee of the 1970 World Cup. The scientifization undertaken by the government of President Medici also reached the Physical Education and the sports. The "modern science" was poured off in every discourse relating to the area and to sports. Thus, it was tried to point out how the entrance of science was in Brazilian soccer and how the winning of the 1970 World Cup was used to attempt crystallization image of Brazil as the soccer country. The thesis also approached how it was the attempt of constructing the soccer country, even on the part of Médici government than of people related to him, as the case of João Havelange, president of the Brazilian Sports Confederation (BSC), who made everything to put his interests in front of everything and everyone. The invention of the soccer country departed largely of the union of this personage in collusion with various people involved in the military government, and not only from it, but the multinational corporate executives involved with the soccer games. Furthermore, the creation of the myth Pelé, king of the soccer, also reviewed here, meets everything that combines with the homeland of soccer shoes. At the same time, and finally, the thesis in question examined the construction of Peter Pedrossian University Stadium, better known as Morenão, in Campo Grande city, in the state of Mato Grosso do Sul, one of the stadiums more used as seat of the One Hundred and Fifty Years Cup, fact that is also analyzed for this thesis